2019
DOI: 10.1007/s13201-019-1021-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption isotherm, kinetic and thermodynamic studies for the removal of Pb(II), Cd(II), Zn(II) and Cu(II) ions from aqueous solutions using Albizia lebbeck pods

Abstract: Powdered adsorbent prepared from Albizia lebbeck pods as agricultural waste has been used for the adsorption of Pb(II), Cd(II), Zn(II) and Cu(II) ions from aqueous solutions. The powdered adsorbent was characterized by X-ray diffraction, Fourier transform infrared spectroscopy and Brunauer-Emmett-Teller. Effects of various parameters like contact time, solution pH, initial concentration dosage and temperature were investigated on a batch adsorption system. Equilibrium and kinetic experiments were carried out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(96 citation statements)
references
References 12 publications
6
88
0
2
Order By: Relevance
“…Pb 2+ adsorption of CA–PU45 was due to OH, CO, and NH functional groups, which acted as the binding sites [ 43 ]. Previous studies reported the adsorbate–adsorbent interaction through the electrostatic force [ 44 , 45 ]. Some others have reported that the chelation is responsible for the mechanism of Pb uptake, and the N-containing functional groups (such as NH and N-C=O) serve as the ligand [ 12 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pb 2+ adsorption of CA–PU45 was due to OH, CO, and NH functional groups, which acted as the binding sites [ 43 ]. Previous studies reported the adsorbate–adsorbent interaction through the electrostatic force [ 44 , 45 ]. Some others have reported that the chelation is responsible for the mechanism of Pb uptake, and the N-containing functional groups (such as NH and N-C=O) serve as the ligand [ 12 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another parameter which allows us to determine the applicability of kinetic model is adsorption rate value. At almost similar R 2 and SSE , the adsorption rate values for pseudo-first order model were lower than for the pseudo-second-order model, indicating a lower rate of adsorption [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biosorption capacities at 5 and 10 mg/L initial Cd 2+ concentration were 4.3 and 9.2 µg of Cd 2+ /g of capsules (at 15 min of aqueous solution contact time), respectively ( Figure 6). The probability of biosorption of Cd 2+ on the active sites of the yeast-alginate system increased as Cd 2+ became more concentrated in the aqueous solution, due to an increase in the driving force that overcame the mass transfer resistance of Cd 2+ between the liquid and solid phases [48]. The biosorption capacities at 5 and 10 mg/L initial Cd 2+ concentration were 4.3 and 9.2 µg of Cd 2+ /g of capsules (at 15 min of aqueous solution contact time), respectively ( Figure 6).…”
Section: Batch Biosorption Of CD 2+ By S Cerevisiae-alginate Systemmentioning
confidence: 99%
“…This percentage was higher than the removal efficiency of encapsulated S. cerevisiae in the batch study (51.9% ± 0.7%) using the same concentration and contact time, and even higher than the Cd 2+ removal efficiency of free S. cerevisiae (75.0% ± 0.1%). A possible explanation for the increase in Cd 2+ efficiency when changing from batch to continuous conditions is the increase in the driving force of Cd 2+ due to the constant flux of solution [48].…”
Section: Fixed-bed Column Biosorptionmentioning
confidence: 99%